Comparison of heavy metal (Cd and Pb) distribution in fish cultured in open and closed system - Ag. Ku Mohd. Shahrul Nizam Ak. Jiar. (2007., 2007)
The development aquaculture sectors in Malaysia are rapidly increased. There have several potential aquaculture areas in the west coast of Peninsular Malaysia. Aquaculture consists of two types of systems which are open aquaculture system and closed aquaculture system. Open aquaculture system is aquaculture that done in river where the water always moving while closed aquaculture system is aquaculture that done in pond where the water does not flow. In Malaysia, data on heavy metals in aquaculture area and the cultured organisms are lacking. The aims of this study are to evaluate non-essential metal (Cd and Pb) in cultured fish and to investigate which aquaculture system is better system for culturing fish. Samples of cultured Nile tilapia (Oreochromis niloticus) from Linggi Estuary (open aquaculture system) and Desa Mahkota (closed aquaculture system) were analyzed for Cd and Pb content using atomic absorption spectrophotometer. Non-essential metals (Cd and Pb) are present in both of the aquaculture areas. Concentrations of Cd and Pb in both aquaculture areas are surpassing the standard outlined by the Malaysian Department of Environment. The accumulation of Cd and Pb concentrated in fin, bone and scale. The accumulation of Cd and Pb in muscle is lower but is going beyond the permissible level. High concentration of Cd and Pb may cause harm to human health through consumption of the fish and some measures should taken to prevent the contaminant at this areas.
Project paper (B.S.(Hons.)) - Universiti Putra Malaysia, 2007.